Assessment of the mental health of medical students of the Espírito Santo state, Brazil, during social distancing imposed by COVID-19 (Brazilian Journal of Health Research, 2022)
Introduction: The coronavirus (COVID-19) has unknown characteristics, with high dissemination and lethality. In this context, containment and distancing measures were enforced to decrease the fast spread of the disease and slow or collapse the health system. Objectives: Review of the impacts of the coronavirus pandemic through the assessment of the mental health of medical students, focusing on anxiety and depression. Methods: Data collection which include medical students from Espirito Santo Universities, from 04/18 to 05/03/2020, through an anonymous online self-completion form, composed of three sections: demographic data and information about coronavirus, Hospital Anxiety and Depression Scale (HAD), behaviour and habilities during the social distancing. Results: The final sample comprised 476 people, 70.2% female and 29.1% male, with a 59.7% predominance in the 21 to 25 age group. According to the Hospital Anxiety and Depression Scale scale, 7.1% likely to experience depression and 36.1% anxiety. The consumption of alcohol and other drugs was reported by 46.3% of the interviewees and 6.1% said they had thought about hurt themselves. Conclusion: The social distancing may contribute to the triggering or intensification of depressive and anxious disorders, as well as an increase in the consumption of alcohol and other drugs. Thus, preventive and supportive measures, during periods of pandemics, are necessary to prevent the illness of medical students and future professionals.
Keywords: Mental Disorders; Coronavirus Infections; Pandemics; Medical Students